An Analytical Study Of Jihad In The Qur’an And The Sunnah: Between Linguistic Precision And Historical Contextualization - Douadi FRADI (Akofena)
Abstract: This article addresses a term unique to Islamic legislation and to the Arabic language during the time of divine revelation. The Arabs had not previously known or used this term in their language—not in the pre-Islamic era nor earlier, neither in poetry nor in prose. That term is jihad. This term is generally known for its negative meaning and usage in the present time, and it is associated with terrorism and islamophobia. This study aims to examine the extent to which the term has interacted between stability and evolution among linguists and scholars of Qur’anic exegesis and Hadith interpretation. In addition, this research paper seeks to clarify the true meaning of the term after its usage across different eras by individuals and groups, and to assess the positive and negative impacts of such usage.